Environmental Management of the Recovery Site in Accordance with the DNSH Principle: The Case of Palazzo Lazzaro in Fossa (AQ) - Eleonora Laurini; Marianna Rotilio; Filomena Petacciato (Applied Sciences)
The construction sector, by its very nature complex and multifaceted, is constantly looking for new methods capable of improving the management system of a project, increasing the efficiency and productivity of some operational phases related to careful planning of the works. To date, the aspects related to sustainability are attributable to the materials used and energy consumption of buildings, but the construction phase of a building is the most harmful moment for the environment. This research has as its primary objective the in-depth study of one of the salient aspects of Facility Management: the guarantee of and compliance with environmental standards, in particular during the construction phase. In more detail, the aspect of the acquisition of methodologies for the environmental management of the recovery site will be explored through compliance with the so-called DNSH (Do Not Significant Harm) Principle, introduced by the Recovery and Resilience Facility (RRF), an economic instrument that supports the national recovery and resilience plans (PNRR). Environmental management will be explored through the creation of an environmental sustainability protocol applied to the construction phase and drawn up on the basis of current environmental legislation. The protocol was validated with the application of the ACS (Sustainable Construction Site Certificate) in a case study located in Italy, Palazzo Lazzaro, which is located in the post-earthquake reconstruction areas, in particular, in Fossa (AQ).